1990
DOI: 10.1055/s-0038-1647283
|View full text |Cite
|
Sign up to set email alerts
|

D-Dimer in Local Thrombolytic Therapy with Low Doses of Recombinant Human Tissue-Type Plasminogen Activator (rt-PA) in Patients with Peripheral Arterial Occlusive Disease

Abstract: SummaryThe generation of D-dimer was studied in the course of local thrombolytic therapy of peripheral arterial occlusions with low doses of recombinant human tissue-type plasminogen activator (rt-PA) in 7 patients. Intermittent local application of rt-PA resulted in a marked increase in D-dimer exceeding values usually seen after intravenous application of manifold higher doses used in myocardial infarction. The increase in D-dimer was related to the estimated thrombus size (length of the occlusion) and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Concentrations of D-dimer therefore represent a specific fibrin degradation product and thus are elevated in patients suffering from thromboembolic disorders [17]. The determination of D-dimer concentration is a valid measure for quantifying the efficacy of fibrinolytic therapy [17].…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of D-dimer therefore represent a specific fibrin degradation product and thus are elevated in patients suffering from thromboembolic disorders [17]. The determination of D-dimer concentration is a valid measure for quantifying the efficacy of fibrinolytic therapy [17].…”
Section: Discussionmentioning
confidence: 99%
“…Cross-linking of fibrin occurs when factor XIIIa causes y-chains to bond and subsequent plasmin lysis of cross-linked fibrin releases D-Dimer complexes in varying amounts depending on the extent of lysis of the fibrin polymers. D-Dimer has been studied in patients with various thrombotic disorders such as peripheral arterial disease (25), acute myocardial infarction (26) and coronary heart disease (27) and its high concentration is considered a laboratory marker of thrombosis and activation of fibrinolysis. Since several recent reports indicate that D-Dimer is a good marker in deep venous thrombosis, in future it may well be used in deep venous thrombosis diagnosis (28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…Although the global coagulation tests remain unaffected by lower rt-PA dos age (< 20 mg total dose), a decrease in α 2 -antiplasmin and a rise in D-dimer indicated a low systemic effect during IAT. 39,40 Uncontrolled studies with the pulse-spray technique reported average times of 65 to 93 minutes for complete lysis of deep-seated femoral/crural vessels and arterial bypasses. 41,42 In a large, nonrandomized study, successful thrombolysis was observed in 95% of patients with a mean lysis time of 96 minutes.…”
Section: Thrombolytic Drugs/clinical Resultsmentioning
confidence: 99%
“…Even the lowdose rt-PA regimen results in a minimal systemic effect that cannot be ruled out by normal global hemostatic tests. 39,40 Therefore, patients with atheromatous lesions in the carotid artery or intracardial thrombi are at high risk of suffering cerebral infarction even under low-dose regimens for IAT. Cerebral infarct incidences up to 2% are reported in IAT.…”
Section: Side Effectsmentioning
confidence: 99%